An experience sampling study on the links between daily teacher self-efficacy, need-supportive teaching and student intrinsic motivation - Kupers, Elisa; Loopers, Judith; Albers, Casper; Bakker, Alianne; Minnaert, Alexander (Frontiers in Psychology, 2023)
Why are some teachers more successful at motivating students than others? We know from previous literature that teachers’ self-efficacy relates to the extent in which they engage in need-supportive teaching in the classroom, which in turn relates to student intrinsic motivation. However, teachers’ self-efficacy is hypothesized to be dependent on their previous mastery experiences, e.g. of engaging students in the classroom. This ‘feedback loop’ where the teacher not only influences the student but also the other way around, in a process unfolding over time, can only be investigated empirically with an intensive longitudinal design. This is precisely what we did in the current study. Secondary school teachers (n=4) and students (n=90) participated in an experience sampling study throughout one school year, resulting in a unique dataset with 48-59 repeated measurement points per class. Visual exploration of the time series revealed that teacher self-efficacy can vary substantially from lesson to lesson, with characteristic patterns of stabilization and de-stabilization. We conducted Vector Autoregressive Analysis (VAR) for each of the four cases to test whether, and how, the variables relate to each other over time. We found an ‘overspill effect’ for student motivation, meaning that students’ motivation in today’s lesson predicts their motivation in tomorrow’s lesson. Furthermore, in two cases we found that today’s student motivation predicts tomorrow’s teacher self-efficacy, but not the other way around.